Use of health parameter trends to communicate pet health information in companion animal practice: A mixed methods analysis. (29th January 2022) - Janke, Natasha; Coe, Jason B.; Bernardo, Theresa M.; Dewey, Cate E.; Stone, Elizabeth A.
Abstract: Background: Reviewing patient health parameter trends can strengthen veterinarian–client–patient relationships. The objective of this study is to identify characteristics associated with veterinarians' communication of health parameter trends to companion animal clients. Methods: Using a sequential exploratory mixed methods design, independent pet owner ( n = 27) and veterinarian ( n = 24) focus groups were conducted and analysed via content analysis to assess perceptions of how health parameter trends are communicated by veterinarians. Subsequently, a quantitative assessment of video recorded veterinary appointments ( n = 917) compared characteristics identified in focus groups with health parameter trend discussions in practice. A mixed logistic model was used to assess characteristics associated with the occurrence of weight trend discussions. Results: Fifteen characteristics relating to veterinarians' use of health parameter trends were identified across focus groups. Veterinarians discussed 77 health parameter trends in relation to bodyweight (57/77), blood work (15/77) and other health parameters (5/77), within 73 (73/917) appointments. The odds of a weight trend discussion were higher if the veterinarian identified the pet as overweight or obese compared to an ideal bodyweight (odds ratio (OR) = 2.17; 95% confidence interval (CI) = 1.15–4.09; p = 0.016). Conclusion: Mention of a health parameter trend was uncommon and rarely included use of visual aids. Health parameter trends related to bodyweight were discussed reactively, rather than proactively.